Penguatan Pendidikan Karakter di Sekolah Dasar Islam Terpadu Al-Manar Pangkalan Bun Kabupaten Kotawaringin Barat - Sri Handayani; Holten Sion; Abdul Rahman Azahari (Journal of Environment and Management, 2020)
School is a place for students to seek knowledge, to hone or to form a good character. Student moral deviation, on the other hand, is something that still happens in schools. This study aims to describe and to analyze the planning, strengthening, assessment, as well as supporting and inhibiting factors of character education at SDIT Al-Manar Pangkalan Bun, Kotawaringin Barat Regency. Respondents consisted of the Headmaster, Vice Headmaster for Student Affairs, Vice Headmaster for Curriculum, and teachers who were determined by the snowball technique. Data obtained through interviews, observation and documentation. Data were analyzed through data reduction, data presentation and drawing conclusions. The results of this study indicate that, first, the planning made by the school has referred to the procedure. Second, the implementation of strengthening character education enrichment refers to the plans that have been made. Third, the assessment of strengthening character education can be seen through the report of attitude assessment. Fourth, strengthening character education is carried out through habituation. Fifth, the inhibiting factors for strengthening character education include lax teacher commitment, lack of student awareness, and lack of parental care.